BURNOUT SYNDROME IN PATIENTS WITH WORKPLACE HYPERTENSION - Yu. P. Zinchenko; E. I. Pervichko; O. D. Ostroumova (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study the presence, severity and qualitative characteristics of «burnout syndrome» in patients with «workplace hypertension» (WPH), in comparison with patients with essential hypertension and healthy people.Material and methods. Untreated patients with hypertension stage II, degree 1-2 (n=170; age 32-52 years; mean age 46.7Ѓ}4.1 years) were examined. Group 1 included 85 patients with WPH (mean age 44.7Ѓ}4.3 years) and Group 2 included 85 patients without WPH (mean age 47.4Ѓ}4.5 years). The duration of hypertension on average was 7.2Ѓ}2.6 years and was comparable in both groups. The control group included 82 healthy subjects (mean age 44.9Ѓ}3.1 years). The Russian version of the Maslach Burnout Inventory (MBI) was used to diagnose «burnout syndrome».Results. Signs of «burnout syndrome» were found in the hypertensive patients of both groups. The high and medium levels of the «burnout syndrome» severity according to all three analyzed factors (emotional exhaustion, dehumanization/depersonification, and personal achievements) were found in 59% of WPH patients, in 36% of hypertensive patients without WPH, and in 9% of healthy individuals. Most of WPH patients had high emotional exhaustion compared with other groups (27.5Ѓ}3.67 points vs 24.6Ѓ}4.3 and 20.1Ѓ}5.7 points in group 2, and group of healthy, respectively; p<0.05). Hypertensive men rated themselves as less successful professionally in comparison with women. Hypertensive women were more prone to emotional exhaustion and dehumanization/depersonification in comparison with men. Conclusion. Signs of «burnout syndrome» were found significantly more often in hypertensive patients in both groups than in healthy people. Medium and high intensity of all forms of «burnout syndrome» occurred in patients with WPH in comparison with healthy people and hypertensive patients without WPH.